Guidelines for neonatal parenteral nutrition - Pereira-Da-silva, Luís (2019)
This update of the guidelines for neonatal parenteral nutrition (PN) prescription is divided into two parts:-Part I, which is included in the same issue of the journal, wherein the general aspects and criteria for fluids, energy, and macronutrients prescriptions, particularly for very and extremely preterm infants, are reviewed.-Part II, which is included herein, wherein the criteria for micronutrients prescription, recommendations for either using individualized prescription with hospital pharmacy compounding or commercial ready-to-use solutions, and PN recommendations in particular clinical conditions are reviewed. Levels of evidence (LoE) and recommendation grades (RG) used in the updated guidelines of the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and the European Society for Clinical Nutrition and Metabolism (ESPEN), supported by the European Society of Paediatric Research (ESPR) together with the Chinese Society of Parenteral and Enteral Nutrition (CSPEN)1 are adopted in this document and shown in the Appendix 1. Appendix 2 provides a table for the rapid consulting of a complete PN prescription in preterm infants.